Pertumbuhan Dan Hasil Tanaman Kangkung Darat(Ipomeareptans Poir) Diberi Trichokompos Jerami Padi - Adnan, Adyan; Rasyad, Aslim; ', Armaini (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
Kang kong (Ipomeareptans Poir) is popular and tasty vegetable mainly grown in tropical asia. In this experiment, we tried to apply rice hay trichocompost to look at if the trichocompost could be utilized for fertilizer in cultivating kang kong. The research was conducted at the Agriculture Experiment Station, University of Riau from June to July 2013. Five rates of trichocompost was applied and arranged in a randomized block design with four replications. Two seed of kang kong were planted each planting hill with planting space of 20 cm x 30 cm in. Plot size was 1,0 m in length and 1,5 m wide.Observations were made for plant height, shoot-root ratio, number of leaves per plant, leaf canopy area, and fresh weight per plant. The results showed that rice hay trichokompost improved plant growth, mainly in plant height, number of leaves and increased production as represented by vegetable fresh weight. However,leaf canopy area and shoot-root ratio showed no significant differences among the rate of trichokompost. The research suggested that rice hay trichocompost may be applied to the rate of 12 tons / ha in order to obtain better growth and higher fresh vegetable yield. Keyword : vegetable, kang kong, trichocompost